Effect of a recombinant Lys49PLA2 myotoxin and Lys49PLA2-derived synthetic peptides from Agkistrodon species on membrane permeability to water - Leite, R. S. (2004)
The aim of this work was to study the effect of recombinant ACL myotoxin, a Lys49PLA2 from Agkistrodon contortrix laticinctus snake venom and Lys49PLA2-derived synthetic peptides corresponding to the region 115–129 of venom of the two different Agkistrodon species on water permeability in the toad urinary bladder. The water flow through the membrane was measured gravimetrically in bag preparations of the bladder. The addition of recombinant ACL myotoxin-MBP (maltose binding protein) fusion protein (10 nM) to the bathing solution significantly increased (above 60%) the water transport compared with the control hemibladders. The addition of the Lys49PLA2-derived synthetic peptides in several concentrations to the bathing solution did not affect the water transport across membrane. These results suggest that the ACL myotoxin effect on water transport is not related to the cytotoxic C-terminal region.